Electrochemical Investigation of Ethylene Glycol as Corrosion Inhibitor of Al 5052 - Habibi; Nikitasari, Arini; Saifudin; Kusumastuti; Musabikha; Prifiharni; Irawan; Priyotomo; Riastuti (BRIN Publishing (Penerbit BRIN), 2024)
Nowadays, electric cars use Al 5052 in the cooling pad of the battery coolant system. Corrosion behavior study of Al 5052 by coolant is essential in the automotive industry. Ethylene glycol is the main compound of the battery coolant system that can inhibit the corrosion process of aluminum alloys. The corrosion inhibition performance of ethylene glycol (EG) for Al 5052 surface in 3.5% NaCl solution has been studied using electrochemical measurements such as potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) in various concentrations of EG up to 50% and a temperature range from 30oC to 60oC. Based on results, EG can inhibit the corrosion process of Al 5052. The corrosion rate (CR) of coolant containing EG decreases with increasing that concentration in various temperatures, and the CR of the coolant rises with the increased temperatures. The inhibition efficiency of coolant boosts with the increase in EG concentration in each operational temperature and the highest up to 75% at 60oC with 50% of EG concentration.